Communicating social and environmental issues effectively - Reed, Betsy (PRCA practice guides., 2020)
This is the definitive guide to planning and delivering great communications on complex social and environmental issues. Including real-world case studies, practical exercises and clear frameworks, this book helps leaders, managers and marketing professionals plan, risk-proof and execute effective communications strategies.